The effectiveness of promotional tools toward society awareness of LA 21 (Local Agenda 21) done by Jempol District Council / Nor Ezlin Maaseh - Maaseh, Nor Ezlin (Faculty of Business and Management, 2014)
Issue and problem: This topic to study how promotional tool will increase society awareness and knowledge of society towards environment at Jempol. So that, the Local Agenda 2(LA21) is exited to encourage people at Jempol District Council love and appreciate their environment. The party involved in causing the Local Agenda 21 was established to provide the community aware of their responsibilities toward environment in the area.